(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
Over the years, significant transformations in the manufacturing sector have been attributed to technology integration and government policies. This has resulted in the emergence of the next generation of business formation, strategies, practices, and overall planning. The issues of managing sustainable manufacturing that SMEs of Saudi Arabia face include Heading and Planning, International Competition, and Financing. In all these areas, it is for this reason that Saudi Arabian SMEs need cooperation to enhance competitiveness and improve their economic welfare and innovation. The current systematic literature review used an extensive search strategy, including databases to identify sources such as Scopus, Web of Science, and Google Scholar, among other databases. The articles on the effects of Collaborative strategic marketing on the sustainable growth & competitive advantage of Saudi Arabian SMEs that were published between 2018 and 2024 were selected. Of all the articles reviewed, 6,550 were identified, and 18 were used in the study after applying the following exclusion criteria. A systematic evaluation was conducted to evaluate two research objectives (RO). The first RO highlighted how collaborative strategic marketing contributed to the development of SMEs, while the second RO also showed that collaborative strategic marketing contributed to the achievement of competitiveness. The results exposed some of the issues that need to be addressed in Saudi Arabian SMEs: strategic orientation, competition from international firms, and the need for more capital. The study also noted that enhancing SME cooperation can greatly impact their digital transformation and innovation.